Accounting for Accidents: Social Costs of Personal Injuries - Gaskins, Richard (Victoria University of Wellington Law Review, 2010)
This short article places the current controversy over the funding of the Accident Compensation regime within the wider context of the original Woodhouse vision of a system that directly deals with, and consequentially alleviates, the wider Social costs of accidents and their impact on individuals. Gaskins argues that an over focus on the "Programme costs" of administering the current scheme risks ignoring the real originality of that vision by focusing simply on the cost of providing benefits rather than on reducing the costs that accidents to society and the individuals that suffer accidents.